2021
DOI: 10.1098/rspb.2021.1787
|View full text |Cite
|
Sign up to set email alerts
|

Fitness benefits of dietary restriction

Abstract: Dietary restriction (DR) improves survival across a wide range of taxa yet remains poorly understood. The key unresolved question is whether this evolutionarily conserved response to temporary lack of food is adaptive. Recent work suggests that early-life DR reduces survival and reproduction when nutrients subsequently become plentiful, thereby challenging adaptive explanations. A new hypothesis maintains that increased survival under DR results from reduced costs of overfeeding. We tested the adaptive value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 52 publications
5
22
1
Order By: Relevance
“…Female reproduction increased, which compensated for the period of reduced nutrient intake, but it did so in conjunction with a reduction in offspring survival. A similar refeedingrelated increase in reproduction following transient fasting was recently reported in Drosophila melanogaster [7].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Female reproduction increased, which compensated for the period of reduced nutrient intake, but it did so in conjunction with a reduction in offspring survival. A similar refeedingrelated increase in reproduction following transient fasting was recently reported in Drosophila melanogaster [7].…”
Section: Discussionsupporting
confidence: 84%
“…Whereas reduced reproduction during fasting could be adaptive when resources are limited, reducing the likelihood of producing offspring into a resource-poor environment and increasing the likelihood of surviving until the environment becomes resource-rich again, there is uncertainty about the effects of DR on survival and reproduction upon refeeding. Indeed, recent work in Drosophila melanogaster has shown that upon exiting a period of DR, not only is there an increase in mortality [6][7][8] but, under some circumstances, there is no compensation for this survival decline with increased fecundity, suggesting an overall cost of the DR response [5]. However, more recently work by Sultanova et al (2021) has shown a contrasting effect, with increased fecundity and mating behaviour in post-DR flies who suffered a similar increase in mortality [6].…”
Section: Introductionmentioning
confidence: 99%
“…According to this "adaptive resource reallocation" hypothesis, DR induces a reallocation of metabolic resources from reproduction to somatic maintenance, and an upregulation of cellular recycling and repair processes such as apoptosis, because these responses reduce mortality and thereby increase the probability of surviving until resources become abundant again and reproduction can resume. This hypothesis is supported by evidence that Drosophila melanogaster females are able to resume full reproduction after a period of DR (Sultanova et al 2021), although increased nutrient abundance following a period of DR can result in elevated mortality that could negate the reproductive gains (McCracken et al 2020).…”
Section: Introductionmentioning
confidence: 95%
“…Note that female reproductive output is denoted as a rate per 24 hr, for better comparison between treatment periods and mating periods (regardless of the treatment). (Levins, 1969;Shreve et al, 2004) and food availability (Sultanova et al, 2021). Interestingly, in our experiment, not only did females cease to increase their reproductive effort when dead conspecifics were removed, but they actually significantly reduced it compared to controls.…”
Section: Perception Of Dead Conspecifics Triggers a Quick Strategic A...mentioning
confidence: 39%
“…In fact, the evolution of reversible plasticity in response to short‐term stressful events is dependent on highly reliable cues and minimum response delays (Gabriel, 2005). For instance, rapid reversible plasticity has been documented in D. melanogaster following changes in environmental temperature (Levins, 1969; Shreve et al, 2004) and food availability (Sultanova et al, 2021). Interestingly, in our experiment, not only did females cease to increase their reproductive effort when dead conspecifics were removed, but they actually significantly reduced it compared to controls.…”
Section: Discussionmentioning
confidence: 99%